Study on the quality of life at work at the Federal Institute of Mato Grosso - Campus Pontes e Lacerda-MT (Research, Society and Development, 2019)
Institutions of education are treated like any business organization in administrative terms, having external and internal influences, and the work of its employees is directly influenced by Quality of Life at Work (QVT). The present article is methodologically qualitative and aims to analyze the Quality of Life at Work (QVT) the Administrative Servants of the Federal Institute of Mato Grosso - Campus Pontes e Lacerda, in relation to work safety, occupational health and accident prevention, as well as as its origin and historical evolution, conceptual aspects, determining factors. The specific objective is to identify the actions developed by the Institute in relation to QVT and the well-being of the servers of the administrative sector and to know the level of satisfaction of them in relation to the program. The methods and techniques used in the study were supported by the discourses of several theorists of scientific research, and the data were collected through questionnaires and internship observations at the institution. In the analysis of the results we can observe that there is interest of the institution in promoting an atmosphere conducive to the servants, as well as they know the importance and they know what it has to do to have QVT, but they treat the subject with lightness. At the conclusion of the topic we can see that few have real interest in the subject addressed, not giving due value to what is being offered to improve the quality of life of the servers, but if we seek to have longevity, we have to worry about the subject and do our life goal.